PENDAMPINGAN PROGRAM KAMPUS MENGAJAR ANGKATAN 7 UNTUK MENINGKATKAN LITERASI DAN NUMERASI DI SDN 1 ARYOJEDING KABUPATEN TULUNGAGUNG - Maskur Maskur; Muhammad Baitul Askha; Sindy Dwi Ariska; Sukma Putri Yoshanti Hadisurya (P3M Politeknik Negeri Malang, 2024)
The Campus Teaching Batch 7 program aims to improve literacy and numeracy at SDN 1 Aryojeding, Tulungagung Regency, through comprehensive mentoring. The program involves students as agents of change who collaborate with teachers in designing and implementing innovative learning strategies. The methods used include observations, interviews, and pre- and post-intervention evaluations to measure the effectiveness of the program. Preliminary results show a significant improvement in students' reading and numeracy skills after participating in this program. Intensive mentoring and the use of interactive learning media proved effective in motivating students and improving their understanding of basic literacy and numeracy concepts. In addition, the program also succeeded in improving teachers' skills through a sustainable learning model. The success of this program shows the importance of collaboration between universities and primary schools in creating a better learning environment. It is hoped that this mentoring model can be adapted and applied in other schools to improve the quality of basic education in Indonesia.